2022
DOI: 10.5964/ijpr.7217
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in predictors of relationship satisfaction: The effects of dyadic coping, love, sexual motivation and having children

Abstract: The present study explored sex differences in the predictors of relationship satisfaction (dyadic coping, love, sexual motivation, having children). A total of 465 Hungarian participants (319 women and 146 men) with a mean age of 33.6 years completed an online test battery comprising four self-report measures. The results revealed that women’s relationship satisfaction had more significant predictors than men’s, and half of the common predictors showed significant sex differences. Men’s satisfaction was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Our data confirm that participants perceive sugar relations as part of short-term mating (positive correlation with unrestricted sociosexuality). This may explain why men are more open to it, as several studies have found marked gender differences in sexual drive in the same direction (e.g., Buss & Schmitt, 1993 , 2019 ; Frankenbach et al, 2022 ; Meskó et al, 2022a , 2022b , 2022c ; Trivers, 1972 ; Walter et al, 2020 ). However, it should be noted that women who engage in sugar relationships also face significant peer stigma (e.g., Ernst et al, 2021 ; Grittner & Walsh, 2020 ; Johansson Wilén & Gunnarsson, 2023 ; Scull, 2022 ), which is also likely to play a role in the higher rejection of this sexual activity among women compared to men.…”
Section: Discussionmentioning
confidence: 95%
“…Our data confirm that participants perceive sugar relations as part of short-term mating (positive correlation with unrestricted sociosexuality). This may explain why men are more open to it, as several studies have found marked gender differences in sexual drive in the same direction (e.g., Buss & Schmitt, 1993 , 2019 ; Frankenbach et al, 2022 ; Meskó et al, 2022a , 2022b , 2022c ; Trivers, 1972 ; Walter et al, 2020 ). However, it should be noted that women who engage in sugar relationships also face significant peer stigma (e.g., Ernst et al, 2021 ; Grittner & Walsh, 2020 ; Johansson Wilén & Gunnarsson, 2023 ; Scull, 2022 ), which is also likely to play a role in the higher rejection of this sexual activity among women compared to men.…”
Section: Discussionmentioning
confidence: 95%